1996
DOI: 10.1074/jbc.271.48.30360
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of cDNA Encoding Rat Very Long-chain Acyl-CoA Synthetase

Abstract: The cDNA encoding rat very long-chain acyl-CoA synthetase (VLACS) was cloned, using degenerative primers synthesized according to the partial amino acid sequences of the peptide fragments of the purified rat liver enzyme. The longest cDNA insert was 2972 base pairs with a 1860-base pair open reading frame encoding 620 amino acids. The calculated molecular mass of 70,692 daltons was consistent with size of the purified enzyme. In Northern blot analysis, a single band was detected at the position of about 3 kilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 40 publications
2
91
0
Order By: Relevance
“…Figure 5 shows the phylogenetic tree of the comparison of the translation of rBAL with the sequences of six very long-chain acyl-CoA synthetases (VLACS) and two very long-chain acyl-CoA synthetase related proteins. rBAL is 65.2-65.5% similar and 42.3-43.9% identical to VLACS proteins cloned from rat (14), mouse (15), and human (16,17). rBAL is most homologous to a mouse VLACSrelated protein (87.2% identity, 93.3% similarity) (18).…”
Section: Expression Of Rbal-1 In Sf9 Insect Cellsmentioning
confidence: 85%
“…Figure 5 shows the phylogenetic tree of the comparison of the translation of rBAL with the sequences of six very long-chain acyl-CoA synthetases (VLACS) and two very long-chain acyl-CoA synthetase related proteins. rBAL is 65.2-65.5% similar and 42.3-43.9% identical to VLACS proteins cloned from rat (14), mouse (15), and human (16,17). rBAL is most homologous to a mouse VLACSrelated protein (87.2% identity, 93.3% similarity) (18).…”
Section: Expression Of Rbal-1 In Sf9 Insect Cellsmentioning
confidence: 85%
“…Sequence analysis of cloned FATP family members revealed two sequence motifs indicative of acyl-CoA synthetases. Subsequent studies have demonstrated that the overexpression of FATP1, FATP2, or FATP4 in COS1 cells increases cell-associated acyl-CoA synthetase activities (11,26,27). Moreover, mutation of serine 250 to alanine significantly reduced fatty acid uptake, suggesting that esterification of fatty acids is coupled to influx (28).…”
Section: Discussionmentioning
confidence: 99%
“…Rotenone is a specific inhibitor of complex I. 3-Mercaptopropionic acid (MPA) inhibits long chain ACADs (30). Kinetic parameters for cytochrome c reduction were calculated using a nonlinear regression algorithm as previously described (29,31).…”
Section: Methodsmentioning
confidence: 99%